ChemInform Abstract: Domino‐Hydroformylation/Aldol Condensation Catalysis: Highly Selective Synthesis of α, β‐Unsaturated Aldehydes from Olefins. Issue 13 (March 2015) - Fang, Xianjie; Jackstell, Ralf; Franke, Robert; Beller, Matthias
Abstract Excellent chemoselectivity is observed in the intermolecular hydroformylation/cross‐aldol condensation reactions of aromatic and aliphatic aldehydes.